KESALAHAN PEMAKAIAN EJAAN DALAM TABLOID “KISAH HIKMAH” TAHUN 2015 - Yulianto Yulianto (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The researcher researches the object to determine how far errors spelling in Kisah Hikmah tabloid 2015. Kisah Hikmah tabloid should be able to use Indonesian as well, but the fact there are many errors spelling are made. This research is aimed to describe the use of errors spelling. This research uses descriptive method by qualitative approach. The data of this research is a written story in Kisah Hikmah tabloid. The source of the data is Kisah Hikmah tabloid published in April to June 2015 addition of 203, 205, and 207 which use technical documentation. In analyze this data use the step: identification, codification, clarification, presentation, interpretation of data, and conclusion. The result shows that te use of error spelling most with 326 mistake, it is showed the errors spelling which Kisah Hikmah tabloid use is high.